Clinical Practices Toward Infection Control During Surgical and Dental Procedures-An Updated Review for Healthcare Professionals - Alhafdi, Khloud Saleh Hamad; Norah Falah Alnawmasi; Jaber Ahmed Jaber Alabdaly; Aesha Humood Mohammed Alosaimi; Rehab Hammod Alotaibi; Yahya Essa Yaqoub Najmi; Yousef Najeh Finkhir Alsharari; Amal Suliman Yahya Aldrsey; Abdullah Mohammad Alhussain; Anood Abdu Yehia Hamammy; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Dental and surgical healthcare environments represent major sources for the transmission of infectious microorganisms because healthcare professionals are routinely exposed to blood, saliva, respiratory secretions, contaminated instruments, and aerosol-generating procedures. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This updated review aimed to evaluate current clinical practices related to infection prevention and control during surgical and dental procedures and to highlight the importance of standard precautions, transmission-based precautions, sterilization, disinfection, hand hygiene, personal protective equipment, and occupational exposure management. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The article reviewed and synthesized current literature and evidence-based recommendations concerning infection control measures within dental and surgical healthcare settings. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The review demonstrated that adherence to comprehensive infection control protocols significantly reduces the risk of pathogen transmission in healthcare environments. Standard precautions including hand hygiene, sterilization, environmental cleaning, and appropriate use of personal protective equipment remain fundamental for all patients regardless of infectious status. Transmission-based precautions are necessary for managing airborne and respiratory infections, particularly during aerosol-generating procedures. Vaccination, proper sharps management, and effective post-exposure protocols were also identified as critical strategies for protecting healthcare workers from occupational infections. Furthermore, enhanced infection control measures introduced during the COVID-19 pandemic improved awareness regarding aerosol management and respiratory protection within dental settings. <span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 12pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Strict implementation of evidence-based infection prevention and control measures is essential for maintaining safe surgical and dental healthcare environments. Continuous education, vaccination, adherence to sterilization standards, and consistent application of standard and transmission-based precautions are necessary to minimize occupational risks, prevent cross-contamination, and improve patient and healthcare worker safety.